PENGEMBANGAN SIKIJANG (SITUS CANDI KIDAL, CANDI JAGO, DAN SITUS PATIRTAAN NGAWONGGO) SEBAGAI MEDIA PEMBELAJARAN IPS KELAS VII DI SMP NEGERI 22 MALANG - Paramita, Septiani Aisyah Ayu; Adi, Khofifatu Rohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop learning media based on mobile learning  by utilizing the help of power point and iSpring suite application in learning Social Sciences, especially on local history material of the region where students live in SMP Negeri 22 Malang. This research is a type of Research and Development (R&D) that refers to the ADDIE development method. The results of this study indicate that the validation of the material aspect obtained a score of 81.9%, the media aspect was 96.25%, and the results of the trial of potential users resulted in a total score of 96.9%. Based on these achievements, the SIKIJANG learning media (Kidal Temple Site, Jago Temple, and Ngawonggo Patirtaan) is categorized as “very feasible” media for use in learning Social Science grade VII at the junior high school / MTs level.